Toleransi dan Tenggang Rasa: Kajian Budaya Melayu Riau dalam Dinamika Multikulturalisme - Yanti, Annisa Darma; Andriani, Tuti; Syafiuddin, Fauzan Azima (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
Tolerance is an essential foundation in a culturally diverse society. Within the context of the Riau Malay community, the concept of tolerance holds deep and complex meanings. Tolerance must be accurately described, as practicing religious tolerance improperly can actually undermine the religion itself. Malays have various values of tolerance expressed through various vocabularies such as openness, diversity, empathy, mutual cooperation, and solidarity. This type of research is known as library research or more commonly referred to as a literature review. This research employs a qualitative approach to address the issues and research focus. The analytical technique used is Descriptive Analysis. In this process, the first step is data classification. Data analysis, also known as data processing and interpretation, is crucial. In social interaction, the Malay ethnicity poses no threat to followers of other religions. In the minds of Malay youths, there is no concept of intervening in other religions. Therefore, the entire Malay world is recognized as the Malay Land (Tanah Jawi) because the majority of its inhabitants are Muslims, use Malay as the widespread language of communication, and practice customs and cultures infused with Islam. Islam in the Malay realm signifies the profound image of the arrival of Islam, which deeply influences the conscience of the Malay people in the archipelago. This is crucial to consider as it also greatly influences the arts and culture of the archipelago.